2022
DOI: 10.3389/fendo.2022.854142
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Association Between Obstructive Sleep Apnea Hypopnea Syndrome Complicated With Coronary Heart Disease and Inflammatory Factors, Glycolipid Metabolism, Obesity, and Insulin Resistance

Abstract: The aim of this study is to explore the association between obstructive sleep apnea hypopnea syndrome (OSAHS) complicated with coronary heart disease (CHD) and inflammatory factors, glycolipid metabolism, obesity, and insulin resistance. A total of 400 patients diagnosed with OSAHS who underwent polysomnography (PSG) monitoring in the Sleep Diagnosis and Treatment Center of Beijing Luhe Hospital from March 2015 to September 2018 were selected and divided into the OSAHS group (n = 200) and the OSAHS + CHD group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Studies have also confirmed a close correlation between fasting blood glucose levels and blood pressure levels and identified it as an independent risk factor for elevated blood pressure [34]. Furthermore, we found that patient age, AHI score, uric acid levels, and fasting blood glucose levels all influence IR [35][36][37][38][39]. This may explain why IR has the highest HR value among quantifiable indicators in independent risk factors while also suggesting that IR is a major cause for the progression from high blood pressure to RH.…”
Section: Discussionsupporting
confidence: 66%
“…Studies have also confirmed a close correlation between fasting blood glucose levels and blood pressure levels and identified it as an independent risk factor for elevated blood pressure [34]. Furthermore, we found that patient age, AHI score, uric acid levels, and fasting blood glucose levels all influence IR [35][36][37][38][39]. This may explain why IR has the highest HR value among quantifiable indicators in independent risk factors while also suggesting that IR is a major cause for the progression from high blood pressure to RH.…”
Section: Discussionsupporting
confidence: 66%
“…High circulating lipids, particularly low-density lipoprotein cholesterol, deposited in the coronary arterial wall can cause endothelial cell damage and inflammation, promote plaque formation and rupture, and lead to myocardial ischemia and even necrosis [44]. Previous studies have also shown that poor sleep or pro-oxidant dietary and lifestyle behaviours, including sleep apnea, short sleep duration, unhealthy diet (low in fiber and high in meat), and low PA may lead to CHD caused by abnormal glycolipid metabolism, endothelial dysfunction, oxidative stress, and inflammation [45][46][47][48]. Therefore, sleep behaviours, OBS, and hyperlipidaemia may have a synergistic effect on CHD through common pathways, which has also been indicated in our findings that the suggestive interaction correlation was found between the combined unhealthy sleep patterns, pro-oxidant OBS, and hyperlipidaemia.…”
Section: Discussionmentioning
confidence: 99%